STRATEGI IMPLEMENTASI KEGIATAN MASA PENGENALAN LINGKUNGAN SEKOLAH (MPLS) VIRTUAL DI SEKOLAH DASAR ISLAM TERPADU - Yetty Faridatul Ulfah (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2022)
This study has purposes to investigate the strategy of online students’ orientation (MPLS) implementation and the implementation of students’ orientation activities at SDIT Ar Risalah and SDIT Taqiyya Rosyida in district Kartasura, Sukoharjo. This study method employed descriptive qualitative research. Data collection tools used observation, interview and document studies. The results of this study reveal that there are three strategies for implementing online students’ orientation activities, and basically, the themes of the four-day students’ orientation activities at SDIT Ar Risalah and SDIT Taqiyya Rosyida are almost the same, namely introduction of teachers and staff, the school environment, character education, and the curriculum. The platform often used by SDIT Ar Risalah and SDIT Taqiyya Rosyida in implementing virtual students’ orientation activity is WhatsApp groups. It is used as a mean of coordination and initial communication between teachers, parents and students. Other online platforms, such as Google Meet, Youtube, and Twibbon are also used as the tool for supporting virtual students’ orientation activities.